Analysis Of Interest In Implementing Halal Certification Among MSMEs In Medan City - Hayati, Fitri; Armaya, Adelia Ayu; Nurul Zulia Lubis, Putri (Universitas Islam Negeri Sumatera Utara, 2023)
To support the progress of their business, MSMEs must carry out halal certification, which is issued by the government. Halal certification also offers new opportunities for economic growth and development, especially in the halal food industry. The aim of this research is to provide broader knowledge to MSMEs who do not yet have halal certificates for food and beverage products, that halal certificates have a big influence on business progress because they create a sense of confidence in consumers towards halal drinks and food. The research method used is a quantitative method by asking questions in the form of a questionnaire generally using a Likert scale (Scale 1-5 (strongly disagree - strongly agree). The conclusion obtained from the research results is that it was found that there is still a lack of knowledge in MSMEs about halal certification However, these MSMEs have the desire to apply for halal certification.